Riscos ergonômicos no serviço hospitalar de limpeza: estudo convergente-assistencial para a prevenção da dor musculoesquelética - Luz, Emanuelli Mancio Ferreira da (2021)
This research had as object of study the analysis of exposure to ergonomic risks in the Hospital Cleaning Service and the occurrence of Musculoskeletal Pain (MSD). It aimed to collectively build and validate a Continuing Education Program to minimize the occurrence of MSD, based on the assessment and perception of ergonomic risks in SHL workers at a teaching hospital in Rio Grande do Sul. Convergent Care Research, with the production of data outlined by mixed methods research, reld from de September 2018 to July 2019. The methodological strategy of the parallel convergent project was performed through observation, photographic records, questionnaires and convergence groups. Systematic observation was performed using a structured script, field diary and photographic records of body postures, totaling 212 hours. The eligible population consisted of 152 workers. Of these, 149 (98%) responded to a questionnaire containing sociodemographic, labor and health variables; Nordic Musculoskeletal Questionnaire and the Corllet and Manenica Diagram. Six convergence groups were held with the participation, on average, of eight managers and 12 workers. The observation, questionnaire and group notes were analyzed according to the sequential process of the Convergent Care Research: apprehension, synthesis, theorization and transference. Qualitative data were submitted to Minayo's thematic analysis. The quantitative ones were analyzed using descriptive and inferential statistics. The ethical precepts of Resolution 466/2012 of the National Health Council and approval of the Research Ethics Committee, opinion number 2,821,335, were complied with. There was a predominance of female workers (89.9%), with a mean age of 44.7 years (±8.05), complete high school (36.2%), working in the daytime (76.5%), for less than one year (59.7%), with a workload of six hours a day (45%), medical diagnosis of musculoskeletal disorders (31.2%), using anti-inflammatory drugs (48.3%), sedentary (64, 4%) and obese (36.2%). The prevalence of MSD, in the seven days prior to the interview, by anatomical region was: lumbar spine (42.3%), ankles or feet (28.2%), wrists or hands (27.5%), upper back (25.5%) and shoulders (23.5%). The associated factors were: selfmedication and pain in the lower back (p=0.020) and shoulders (p=0.026); sedentary lifestyle, eight hours of sleep a day and pain in the ankles or feet (p=0.041 and p=0.039); ex-smoking, use of medication and pain in the wrists or hands (p=0.015 and p=0.004). Participants expanded the concept of ergonomic risk, which included the social devaluation of the profession and the psychosocial aspects of work. Mixing the data evidenced the exposure of workers to ergonomic risk in the use of equipment not adapted to psychophysiological needs and non-functional shoes; in repetitive movements, physical overload of body segments and unfavorable anatomical postures, which may be related to MSD. Interdisciplinary, educational and therapeutic interventions were carried out in the extension project “Educational practices to promote the health of SHL workers”. These included ergonomic education, auriculotherapy and gymnastics at work. The main point of convergence was the teaching-learning group actions, which culminated in the collective proposition of the “Continuing Education Program: a look at health and ergonomics in hospital cleaning work”, validated with an agreement rate of 0.95 . From the results, recommendations were made for improvements directed to workers and the management of the SHL regarding the minimization of ergonomic and DME risks.